Status of Solid Waste Generation at Jahangirnagar University Campus and Development of a Suitable Management Plan - Saadat, AHM; Parvin, F; Alam, ATMJ; Kamal, AKI (Journal of Environmental Science and Natural Resources, 2012)
Present status of solid waste generation of Jahangirnagar University campus was assessed and its probable utilization was examined and a suitable management option is prescribed. Study includes waste generation in the teachers and staff quarters, central cafeteria and different students halls. It is found that every day about five metric tons of waste generated from different locations and they are dumped into the open environment and deteriorating the environment. Calculations suggest that 30 kW/h electricity along with 300 metric tons of compost can be generated from the organic part of the waste in the campus every year. This electricity can be used for continuous electrification of research laboratories or class rooms. The compost generated from the solid waste, can replace the organic and inorganic manure for gardening in the campus which can save a handsome amount of money from the yearly budget of Jahangirnagar University in this sector. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11579 J. Environ. Sci. & Natural Resources, 5(1): 187 - 191, 2012